Overview of the Biochemical Potential of Solanum Nigrum - Abd alKhudhur salman, Noor (University of Thi-Qar Journal of Science, 2024)
Solanum nigrum is known locally as the nightshadesamily, and it is considered one of the widespread plants that possess great biochemical potential. This review dealt with providing a comprehensive summary of the biochemistry of this plant, as it contains Solanum nigrum. It contains an important group of biologically active substances, including flavonoids, and some phenolic derivatives. It also contains some alkaloids, epoxy derivatives, and other important compounds. These substances have important biological activity, including significant and powerful antioxidant and anti-inflammatory properties, as well as strong antimicrobial and anti-cancer properties, and other medically important properties. This plant has been used for medicinal purposes for a long time in treating many diseases. Finally, this review indicates the wide biological diversity in biochemistry. The study also touched on some potential applications in various fields, including nutrition and medicine.